Orbital angular momentum light interacted with double quantum dot-metal nanoparticle hybrid structure under spontaneous coherence - Mohanad Ahmed Abdulmahdi; Amin Habbeb Al-Khursan (Scientific Reports)
Abstract This work studies the generation of the orbital angular momentum (OAM) beam in the double quantum dot-metal nanoparticle (DQD-MNP) system under the application of the OAM beam. First, an analytical model is derived to attain the relations of probe and generated fields as a distance function in the DQD-MNP system under OAM applied field and spontaneously generated coherence (SGC) components. The calculation here is of material property; it differs from others by calculating energy states of the DQDs and the computation of the transition momenta between quantum dot (QD)-QD and QD-wetting layer (WL) transitions. The orthogonalized plane wave (OPW) calculates QD-WL transitions and their momenta. The momentum calculation is essential to specify the Rabi frequency of the input field. Such characteristics are not used in earlier models. The results show that SGC is vital in increasing the generated field. The signal field generated in the DQD-MNP system doubles that from the DQD system alone. So, the DQD-MNP system is preferred to the DQD system. The generated field in the DQD-MNP for the strong coupling DQD-MNP system is higher than that for the weak coupling. Increasing the distance separating the DQD-MNP reduces the generated field. Higher OAM number reduce the generated field at a long distance in the device. The model is then extended to study the effect of incoherent pumping ( $$\:R_{inc}$$ ) and the relations are modified to cover this part. The results show that $$\:R_{inc}$$ reduces the generated field. While the results that compare the weak and strong coupling appear for the first, others compare well to the literature.